PENGARUH DANA ZAKAT INFAK DAN SEDEKAH ( ZIS) TERHADAP KEMISKINAN DI KABUPATEN /KOTA PROVINSI ACEH - Yuliana Yuliana; Yulfrita Adamy; Chelliana Adhila (Syiah Kuala University, 2019)
Abstract This study aims to analyze the effect of Zakat, Infaq and Alms to Poverty. The data used in this study were obtained from the Aceh Central Statistics Agency and the Baitul Mal Aceh. Data analysis used panel data with a Fixed Effect Model regression model for the period 2013-2017 in 23 Regencies / Cities in Aceh Province. The results showed that partially the Zakat, Infaq, and Alms (ZIS) variables had a negative and significant effect on poverty in Aceh Province / City with a probability value of 0.0128 less than 0.05. Adjusted R² of 0.99, thus means the variable Zakat, Infaq, Alms (ZIS) is able to explain the poverty variable by 99% and the remaining 1% is influenced by variables or other factors that exist outside the model.